Thinking clockwise - Andrade, Raquel P. (2005)
Throughout the Animal Kingdom, the time of embryonic development is maintained and strictly controlled. Each step of the process is successful only when it occurs at the right time and place. This raises the question: how is time controlled during embryonic development? Time control is particularly crucial during embryo segmentation processes, where the number of generated segments, as well as the time of formation of each segment, is extraordinarily constant and specific for each species. Somitogenesis is the process through which the vertebrate presomitic mesoderm is segmented along its anterior–posterior axis into roundshaped masses of epithelial cells, named somites. In the chick embryo, a new pair of somites is formed every 90 min. The discovery that this clock-like precision is dictated by the somitogenesis molecular clock constituted a landmark in the Developmental Biology field. Several genes exhibit cyclic gene expression in the embryo presomitic mesoderm from which the somites arise, presenting a 90 min oscillation period, the time required to form a pair of somites. The combined levels of dynamic gene expression throughout the presomitic mesoderm enable cells to acquire positional information, thus giving them a notion of time. Anterior–posterior patterning of the vertebrate nervous system also involves partition into discrete territories. This is particularly evident in the hindbrain where overt segmentation occurs. Nevertheless, little is known about the segmentation genes and mechanisms that may be involved. This paper intends to describe the molecular clock associated with vertebrate somitogenesis, suggesting that it may be operating in many other patterning processes.